Analysis of undergraduate cell biology contents in Brazilian public universities. (16th January 2017) - Mermelstein, Claudia; Costa, Manoel Luis
Abstract: The enormous amount of information available in cell biology has created a challenge in selecting the core concepts we should be teaching our undergraduates. One way to define a set of essential core ideas in cell biology is to analyze what a specific cell biology community is teaching their students. Our main objective was to analyze the cell biology content currently being taught in Brazilian universities. We collected the syllabi of cell biology courses from public universities in Brazil and analyzed the frequency of cell biology topics in each course. We also compared the Brazilian data with the contents of a major cell biology textbook. Our analysis showed that while some cell biology topics such as plasma membrane and cytoskeleton was present in ∼100% of the Brazilian curricula analyzed others such as cell signaling and cell differentiation were present in only ∼35%. The average cell biology content taught in the Brazilian universities is quite different from what is presented in the textbook. We discuss several possible explanations for these observations. We also suggest a list with essential cell biology topics for any biological or biomedical undergraduate course. The comparative discussion of cell biology topics presented here could be valuable in other educational contexts.